2023
DOI: 10.1101/2023.01.30.526367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coevolution of the CDCA7-HELLS ICF-related nucleosome remodeling complex and DNA methyltransferases

Abstract: 5-Methylcytosine (5mC) and DNA methyltransferases (DNMTs) are broadly conserved in eukaryotes but are also frequently lost during evolution. The mammalian SNF2 family ATPase HELLS and its plant ortholog DDM1 are critical for the maintenance of 5mC. Mutations in HELLS, its activator subunit CDCA7, and the de novo DNA methyltransferase DNMT3B, cause immunodeficiency-centromeric instability-facial anomalies (ICF) syndrome, a genetic disorder associated with the loss of DNA methylation. We here examine the coevolu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 153 publications
0
14
0
Order By: Relevance
“…Although CDCA7 coevolved with HELLS and the maintenance DNA methyltransferases ( 28 ), their mechanistic link remained unclear. The first hint emerged when we observed that HELLS preferentially accumulated on sperm chromatin after incubation in interphase DNMT1-depleted Xenopus egg extracts (ΔDNMT1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although CDCA7 coevolved with HELLS and the maintenance DNA methyltransferases ( 28 ), their mechanistic link remained unclear. The first hint emerged when we observed that HELLS preferentially accumulated on sperm chromatin after incubation in interphase DNMT1-depleted Xenopus egg extracts (ΔDNMT1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of HELLS and its plant ortholog DDM1 in DNA methylation has been established in vertebrates and in plants ( 1825 ), and it has been suggested that the nucleosome remodeling activity of HELLS/DDM1 facilitates DNA methylation ( 26, 27 ). However, it remains unclear why a role in promoting DNA methylation is uniquely carried out by HELLS/DDM1 among several other coexisting SNF2-family ATPases with similar nucleosome remodeling activity, such as SNF2 (SMARCA2/4), INO80, and ISWI (SMARCA1/5) ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent evolutionary analysis could trace back CDCA7 and HELLS to the last eukaryotic common ancestor (62), suggesting conserved functions in DNA methylation pathways. We find that CDCA7 predominantly targets the B genomic compartment (Fig.…”
Section: Discussionmentioning
confidence: 99%